Peran pemerintah dalam mempromosikan alternatif penyelesaian sengketa di Indonesia - Fawaiq Sayyaf, R. Tanzil (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The Indonesian government has implemented diverse initiatives to foster a nonviolent approach to resolving family law conflicts. The study will examine the involvement of governments and their initiatives in advocating for conflict resolution as a viable method for addressing societal concerns. The aggregation of cases handled by multiple courts led to a prolonged resolution of the recorded concerns. This study will focus on two distinct problem formulations. Firstly, we will discuss the government's role in promoting alternative dispute resolution as a solution to difficulties. Secondly, we will examine why government techniques for implementing alternative conflict resolution are superior to resorting to court proceedings for dispute settlement. This research aims to enhance people's understanding of the government's provision of non-judicial or alternative dispute resolution. The report seeks to analyze the government's initiatives in addressing the issue of Islamic family law. This study will utilize library research and significant data regarding specific government initiatives. This will be accomplished using a legal and normative approach. The study findings indicate that the government is actively promoting alternative methods of resolving disputes, such as mediation. This is being done through the implementation of mediation in the courts, improving legal aid services, enacting laws on a large scale, and encouraging the utilization of information and communication technologies. The strategy is executed by promoting mediation and conciliation in all court proceedings, establishing dispute resolution centers, empowering women to reduce disputes related to women, promoting legal education and awareness, and maximizing the utilization of technology and information.